Islamic Business Ethics In Culture-Based Economic Practice: A Study of the Chinese Muslim Community in Lampung - Diana Ambarwati; M. Atho Mudzhar; Euis Amalia; Desmadi Saharudin (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: This study aims to analyze Islamic business ethics in culture-based economic practices among the Chinese Muslim community in Lampung, focusing on how religious and cultural values are integrated in business activities. Method: This study uses a qualitative descriptive method with a phenomenological approach, collecting data from Chinese Muslim entrepreneurs in Lampung through observation, interviews, and documentation, and analyzing it via data reduction, display, and conclusion drawing. Result: The findings reveal that the business ethics of Chinese Muslims in Lampung are rooted in traditional Chinese values, influenced by universal Confucianism, demonstrating strong adaptability to other value systems. These values generally align with Islamic business ethics and even reinforce one another, except in aspects related to the halal concept and the belief in the divine presence in business activities. These gaps are addressed by incorporating Islamic principles, such as halal compliance and philanthropic practices. Furthermore, the study shows that Chinese Muslim entrepreneurs exhibit a minority cultural character that is open to acculturation with dominant Islamic values, resulting in a harmonious integration of both ethical systems. Implication: This study offers concise theoretical and practical insights into integrating religious and cultural values in business, serving as a reference for ethical business models in multicultural societies. Originality or Novelty: This research introduces the concept of dual embeddedness, highlighting that economic behavior is simultaneously shaped by moral-religious values and socio-cultural structures, thereby extending Granovetter’s embeddedness theory into a religio-cultural context.